Coal tar hydrogenation catalyst, its preparation method and application

CN120827894BActive Publication Date: 2026-10-09CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410478376.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-19
Publication Date
2026-10-09
Estimated Expiration
2044-04-19

AI Technical Summary

Technical Problem

该制备方法分子筛与原料直接混合,煤焦油中的金属和碱性氮沉积在分子筛上,使催化剂快速失活,达不到既能加氢处理又能加氢裂化的目的,且催化剂的制备工艺较为复杂

Benefits of technology

[0045] 1. In the catalyst of the present invention, the support is a gallium-modified silicon-aluminum support; wherein, based on the mass of the gallium-modified silicon-aluminum support, the mass content of gallium oxide is 2.0% to 5.0%, the mass content of silicon dioxide is 20.0% to 60.0%, and the mass content of aluminum oxide is 35.0% to 78.0%; the active metal component includes Mo and Group VIII metal elements; the Mo includes +5 valence Mo; the Group VIII metal elements exist in the catalyst in the form of metal phosphides.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a coal tar hydrogenation catalyst and a preparation method and application thereof. The catalyst comprises a carrier and an active metal component, the carrier is a gallium modified silicon-aluminum carrier, the mass content of gallium oxide in the gallium modified silicon-aluminum carrier is 2.0-5.0% based on the mass of the gallium modified silicon-aluminum carrier, the mass content of silicon dioxide is 20.0-60.0%, and the mass content of aluminum oxide is 35.0-78.0%; the active metal component comprises Mo and a group VIII metal element; the Mo comprises +5 valence Mo; and the group VIII metal element exists in the catalyst in the form of a metal phosphide. The catalyst has high hydrogenation activity, appropriate cracking activity and good stability, and effectively improves the quality and yield of coal tar hydrogenation product oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of coal tar hydrogenation catalyst preparation, specifically relating to a coal tar hydrogenation catalyst, its preparation method, and its application. Background Technology

[0002] Coal tar is a liquid produced during the pyrolysis of coal. Depending on the distillation temperature and process, it can be classified into low-temperature coal tar (450–650℃), medium-temperature coal tar (650–900℃), and high-temperature coal tar (900–1000℃). Currently, the extraction capacity for high-value-added products from coal tar is limited, and most is still used directly as crude fuel, which is not only economically unsustainable but also severely pollutes the environment. However, producing clean fuel oil from coal tar through hydrogenation offers significant economic, social, and environmental benefits.

[0003] Compared to heavy petroleum fractions, coal tar feedstock contains oxygen, a large amount of unsaturated hydrocarbons such as olefins and polycyclic aromatic hydrocarbons, as well as sulfur and nitrogen compounds. It is characterized by high acidity, high gum content, and poor product stability (light stability, storage stability, and oxidation stability). Therefore, it is of great significance to develop coal tar hydrogenation catalysts with strong water resistance, good hydrotreating and impurity removal performance, good hydrogenation performance, and good cracking performance.

[0004] CN108686702A discloses a fluidized bed coal tar hydrotreating-hydrocracking composite catalyst and its preparation method. The catalyst is composed of MoO3, WO3, NiO, alumina, silica molecular sieves, and additives by mass percentage. The catalyst preparation process involves reacting acidified silica-containing raw materials with an alkaline gas to solidify and generate microsphere gels. After drying and calcination, a catalyst support is obtained, and then the active metal component is loaded onto the support to finally obtain the catalyst. However, this preparation method involves direct mixing of the molecular sieve with the raw materials, causing metals and alkaline nitrogen from the coal tar to deposit on the molecular sieve, leading to rapid catalyst deactivation. This fails to achieve the goal of both hydrotreating and hydrocracking, and the catalyst preparation process is relatively complex.

[0005] CN101885984A discloses a combined process for the hydrogenation of coal tar to produce clean fuel oil and its catalyst. The active component of the hydrogenation catalyst in this patent is one or more of Group VIII and Group VIB metal oxides, namely NiO, MoO3, CoO, and WO3, and the support is acid-modified kaolin. Because acid-modified kaolin is used as the support, its pore volume is very small and its acidity is high. Therefore, for coal tar feedstocks with high gum and asphaltenes content, gum and asphaltenes cannot enter the catalyst pores, resulting in more carbon deposits on the catalyst surface, making the catalyst prone to deactivation and resulting in a short operating cycle. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a coal tar hydrogenation catalyst, its preparation method, and its application. This coal tar hydrogenation catalyst exhibits high hydrogenation activity, suitable cracking activity, and good stability, effectively improving the quality and yield of the coal tar hydrogenation product oil.

[0007] The first aspect of this invention provides a coal tar hydrogenation catalyst. The catalyst comprises a support and an active metal component.

[0008] According to the present invention, the carrier is a gallium-modified aluminum-silicon carrier. In the gallium-modified aluminum-silicon carrier, based on the mass of the gallium-modified aluminum-silicon carrier, the mass content of gallium oxide is 2.0%–5.0%, the mass content of silicon dioxide is 20.0%–60.0%, and the mass content of aluminum oxide is 35.0%–78.0%.

[0009] According to the present invention, based on the mass of the catalyst, the mass content of the support is 74% to 83%, the content of Group VIII metals as oxides is 2% to 6%, and the content of molybdenum as oxides is 15% to 20%.

[0010] According to the present invention, the catalyst has the following properties: a specific surface area of ​​150–200 m². 2 / g, pore volume is 0.5~0.8mL / g, mechanical strength is 110~190N / cm, total acid content is 0.2~0.5mmol / g, and the ratio of B acid content to L acid content is 0.35~0.65.

[0011] According to the present invention, the pore size distribution of the catalyst is as follows: the pore volume of pores with a diameter <10 nm accounts for 5% to 10% of the total pore volume, the pore volume of pores with a diameter of 10 to 50 nm accounts for 65% to 80% of the total pore volume, and the pore volume of pores with a diameter >50 nm accounts for 10% to 30% of the total pore volume.

[0012] According to the present invention, the active metal component includes Mo and a Group VIII metal element; the Mo includes +5 valence Mo; the Group VIII metal element exists in the catalyst in the form of a metal phosphide.

[0013] According to the present invention, the catalyst further includes +4 valent Mo and +6 valent Mo.

[0014] According to the present invention, in the catalyst, +5 valence Mo accounts for more than 50% of the total Mo atomically, preferably 55% to 80%. As a non-limiting example, +5 valence Mo accounts for any value of 65%, 68%, 70%, 72%, 75%, or 78% of the total Mo atomically.

[0015] According to the present invention, in the catalyst, the sum of +4 valence Mo and +6 valence Mo accounts for 20% to 45% of the total Mo atoms. More preferably, in the catalyst, +4 valence Mo accounts for 10% to 43% of the total Mo atoms; and +6 valence Mo accounts for 2% to 10% of the total Mo atoms. As a non-limiting example, +4 valence Mo accounts for any value of 15%, 20%, 22%, 25%, 32%, 35%, 38%, or 40% of the total Mo atoms; and +6 valence Mo accounts for any value of 4%, 6%, 8%, or 9% of the total Mo atoms.

[0016] According to the present invention, in the catalyst, +5 valence Mo is preferably molybdenum pentachloride; +4 valence Mo is preferably molybdenum disulfide; and +6 valence Mo is preferably molybdenum oxide.

[0017] According to the present invention, the group VIII metal element is selected from one or more of Fe, Co, and Ni, preferably at least one of Co and Ni, and more preferably Ni.

[0018] A second aspect of the present invention provides a method for preparing the above-mentioned catalyst, comprising:

[0019] (1) A first impregnation solution is obtained by mixing molybdenum source, sulfur source and water, and then impregnated on a support. After drying, catalyst intermediate I is obtained.

[0020] (2) React the catalyst intermediate I described in step (1) with chlorine gas to obtain catalyst intermediate II;

[0021] (3) The catalyst intermediate II described in step (2) is impregnated with a second impregnation solution containing nickel and phosphorus sources, and then cured, dried and calcined to obtain the catalyst.

[0022] According to the present invention, in step (1), the method for preparing the carrier includes:

[0023] (11) Mix and stir the acidic aluminum salt aqueous solution, silicon source, and organic acid to obtain material AI;

[0024] (12) Material AI is subjected to a precipitation reaction with gallium-containing solution and alkaline aluminum salt aqueous solution in parallel flow to obtain material AII;

[0025] (13) The material AII was subjected to hydrothermal treatment with a nonionic surfactant to obtain gallium-modified aluminum silicon material;

[0026] (14) The gallium-modified silicon-aluminum material, adhesive, extrusion aid and water obtained in step (13) are mixed and kneaded, dried and calcined to obtain a catalyst support.

[0027] According to the present invention, in the method for preparing the carrier, the acidic aluminum salt in step (11) is at least one of aluminum sulfate, aluminum chloride or aluminum nitrate, and the concentration of the acidic aluminum salt solution, calculated as Al2O3, is 20-100 g / 100 mL; the silicon source is one or more of water-soluble silicates, water glass, and silica sol, and the concentration of the silicon source, calculated as SiO2, is 30-70 g / 100 mL, and the weight ratio of the silicon source (calculated as SiO2) to the acidic aluminum source (calculated as Al2O3) is 1:1-7:1.

[0028] According to the present invention, in the method for preparing the carrier, the organic acid in step (11) is one or more selected from maleic acid, fumaric acid, adipic acid, tartaric acid, citric acid, oxalic acid, acetic acid, salicylic acid, and malic acid. The mass concentration of the organic acid is 7% to 16%. The amount of organic acid added makes the pH value of the material AI 2 to 4, preferably 3 to 4.

[0029] According to the present invention, in the method for preparing the carrier, the gallium-containing solution in step (12) is a gallium nitrate solution with a concentration of 0.5–2.5 mol / L. The alkaline aluminum salt is at least one of sodium aluminate or potassium aluminate. The concentration of the alkaline aluminum salt solution, calculated as Al2O3, is 20–100 g / 100 mL. The ratio of the co-current flow rates of the gallium-containing solution, the material Al, and the alkaline aluminum salt solution is 1:3–7:1–3. The reaction temperature in step (12) is 60–90 °C, the reaction time is 60–180 minutes, and the pH value is 8.0–9.7. The reaction is preferably carried out under stirring conditions, with a stirring rate of 100–500 rad / min, preferably 150–450 rad / min.

[0030] According to the present invention, in the method for preparing the carrier, the nonionic surfactant in step (13) is selected from one or more of polyethylene glycol, alkylolamide, and polyether; the alkylolamide is one or more of lauroyl diethanolamine and coconut oil fatty acid diethanolamide; the polyether is one or more of AEO-6 and AEO-9; the molecular weight of the polyethylene glycol is 200-1000, preferably 200-700; the amount of the nonionic surfactant added is 0.1%-5% of the mass of the material AII obtained in step (12) based on alumina, preferably 0.5%-3%. The concentration of the nonionic surfactant is 30-70 g / 100 mL.

[0031] According to the present invention, in the method for preparing the carrier, the conditions for the sealing hydrothermal treatment in step (13) are as follows: the hydrothermal treatment temperature is 80–130°C, the time is 3–18 hours, and the heating rate is 8–15°C / min. Preferably, the hydrothermal treatment is performed in two stages: the first stage hydrothermal treatment temperature is 80–110°C, the first stage hydrothermal treatment time is 1–9 hours, and the second stage hydrothermal treatment temperature is 100–130°C, the second stage hydrothermal treatment time is 1–9 hours, wherein the second stage hydrothermal treatment temperature is at least 15°C higher than the first stage hydrothermal treatment temperature, preferably at least 20°C higher. After the reaction, washing and drying can be performed. The drying conditions are: drying at 100–170°C for 1–7 hours.

[0032] According to the present invention, in the preparation method of the carrier, the catalyst carrier preparation process in step (14) involves adding an extrusion aid, a binder, etc., to a gallium-modified silicon-aluminum material, kneading it into a plastic body, and then molding it. The molding can be carried out using conventional molding methods, such as extrusion molding, tablet molding, etc., with extrusion molding being preferred. The amount of extrusion aid added is 1.0 wt% to 4.0 wt% of the gallium-modified silicon-aluminum material; the amount of binder added is 1.0 wt% to 5.0 wt% of the gallium-modified silicon-aluminum material; and the amount of water added is 80.0 wt% to 100.0 wt% of the gallium-modified silicon-aluminum material. The extrusion aid is guar gum powder, and the binder is nitric acid.

[0033] According to the present invention, in the method for preparing the carrier, the drying temperature in step (14) is 120-160°C, the drying time is 2-6 hours, the calcination temperature is 550-800°C, and the calcination time is 4-6 hours.

[0034] According to the present invention, in the method for preparing the catalyst, the molybdenum source in step (1) is selected from at least one of ammonium dimolybdate, ammonium tetramolybdate dihydrate, and ammonium heptamolybdate tetrahydrate; the sulfur source is selected from at least one of thiourea, ammonium sulfide, thioacetamide, and sodium thiosulfate; the mass ratio of the molybdenum source to the sulfur source is 3-5:2-4. In the first impregnation solution, the mass content of the molybdenum source is 25wt%-45wt%.

[0035] According to the present invention, in the method for preparing the catalyst, the impregnation in step (1) can be carried out by spray impregnation, and the impregnation can be carried out by saturated impregnation or supersaturated impregnation. The drying conditions are drying at 100-140°C for 4-8 hours.

[0036] According to the present invention, in the method for preparing the catalyst, in step (2), the purity of the chlorine gas is 96% or higher by volume fraction. The flow rate of the chlorine gas is 2.7 to 6.8 mL / (min·g catalyst intermediate I); and / or, the reaction conditions are as follows: the reaction temperature is 300 to 400 °C, and the reaction time is 40 to 90 min.

[0037] According to the present invention, in the method for preparing the catalyst, the nickel source in step (3) is a soluble salt, such as at least one of nitrates, monohydrogen phosphates, and dihydrogen phosphates; the phosphorus source is selected from at least one of ammonium phosphates, sodium dihydrogen phosphate, disodium hydrogen phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, and phytic acid. In the second impregnation solution, the molar ratio of the nickel source (based on metal element) to the phosphorus source (based on phosphorus element) is 0.3 to 3:1. In the second impregnation solution, the mass content of the nickel source is 40 wt% to 68 wt%.

[0038] According to the present invention, in the preparation method of the catalyst, the impregnation in step (3) can be carried out by spray impregnation, and the impregnation can be carried out by saturated impregnation or supersaturated impregnation.

[0039] According to the present invention, in the method for preparing the catalyst, the conditioning in step (3) involves placing the impregnated sample under sealed conditions at 10–30°C for 6–12 hours. The conditioning pressure is not particularly limited and can be autogenous pressure. And / or, the drying conditions are drying at 100–160°C for 1–8 hours. The calcination conditions are calcination at 480–550°C for 4–8 hours. The drying atmosphere is an oxygen-containing atmosphere. The calcination atmosphere is selected from any one of a nitrogen atmosphere, an inert gas atmosphere, a hydrogen / nitrogen atmosphere, and a hydrogen / inert gas atmosphere, wherein the hydrogen gas fraction in the hydrogen / nitrogen atmosphere and the hydrogen / inert gas atmosphere is 5%–50%.

[0040] The third aspect of the present invention provides the application of the above-described catalyst or the catalyst prepared by the above-described preparation method in the hydrogenation treatment of coal tar.

[0041] According to the present invention, the application conditions are: reaction temperature of 300–420°C; reaction pressure of 5–20 MPa; and liquid hourly space velocity of 0.1–1.5 h⁻¹. -1 The hydrogen-to-oil volume ratio is 100:1 to 1200:1. The reaction pressure is the total pressure.

[0042] According to the present invention, the catalyst needs to be sulfided before application. The sulfidation process is as follows: the catalyst is contacted with a sulfidation liquid and hydrogen to undergo sulfidation. The sulfidation liquid includes a solvent and a sulfur-containing solute; the sulfur-containing solute has a mass content of 4.0% to 15.0% in the sulfidation liquid. The sulfur-containing solute is a sulfur-containing compound with a solubility of more than 10 wt% in the solvent at room temperature, and which decomposes with hydrogen to produce H2S under high temperature conditions. The sulfur-containing solute is preferably at least one of carbon disulfide (CS2), dimethyl sulfide (DMS), dimethyl disulfide (DMDS), and SZ-54. The solvent is hydrotreated diesel with a nitrogen content of not more than 100 μg / g. The purity of the hydrogen is not less than 90% vol%.

[0043] According to the present invention, the vulcanization conditions adopt conventional vulcanization conditions. Preferably, the vulcanization conditions are as follows: the vulcanization process includes low-temperature vulcanization and high-temperature vulcanization. Low-temperature vulcanization stage: heating to 150-260℃ and holding at that temperature for 6-10 hours; high-temperature vulcanization stage: heating to 260-390℃ and holding at that temperature for 5-8 hours. The heating rate to the low-temperature vulcanization stage is 8-12.0℃ / h, the heating rate to the high-temperature vulcanization stage is 5-12.0℃ / h, the flow rate of the vulcanizing liquid is 15-30 mL / (h·g catalyst), the hydrogen pressure is 13.0-18.0 MPa, and the hydrogen flow rate is 80-130 mL / (min·g catalyst).

[0044] Compared with the prior art, the present invention has the following advantages:

[0045] 1. In the catalyst of the present invention, the support is a gallium-modified silicon-aluminum support; wherein, based on the mass of the gallium-modified silicon-aluminum support, the mass content of gallium oxide is 2.0% to 5.0%, the mass content of silicon dioxide is 20.0% to 60.0%, and the mass content of aluminum oxide is 35.0% to 78.0%; the active metal component includes Mo and Group VIII metal elements; the Mo includes +5 valence Mo; the Group VIII metal elements exist in the catalyst in the form of metal phosphides.

[0046] Because the +5 valence molybdenum in the catalyst of this invention is more easily sulfided into +4 valence molybdenum disulfide during the sulfidation process, the rate of molybdenum disulfide formation is accelerated. This leads to a greater likelihood of forming Ni-Mo-S(II) and Brim active sites with a MoS2 framework and metallic nickel on the outer surface in the catalyst. The catalyst of this invention also forms a suitable amount of transition metal phosphides, which are compounds formed by phosphorus atoms inserting into the metal lattice and exhibiting noble metal-like properties. Due to the large size of phosphorus atoms, after bonding with the transition metal, octahedral coordination structures are more easily formed around the phosphorus atoms, placing them at the central position. Therefore, unlike the layered structure of sulfides, the phosphide structure is closer to a spherical shape, exposing more active sites during the catalytic reaction, making it easier for large molecular reactants to approach the active sites on the catalyst surface. This catalyst effectively improves the quality and yield of coal tar hydrogenation product oil.

[0047] 2. In the catalyst preparation process of this invention, the support is first impregnated with an impregnation solution containing a molybdenum source and a sulfur source to obtain intermediate I, which is then reacted with chlorine gas to obtain intermediate II. Finally, intermediate II is impregnated with a nickel-phosphorus impregnation solution to prepare the catalyst. Furthermore, the support is also prepared using a specific method, namely, by using organic acids and Ga modification to prepare the catalyst support. The method of this invention is beneficial for giving the coal tar hydrogenation catalyst suitable pore structure, acid content, and acid distribution. Through the comprehensive coordination of each step, the catalyst support and active metal work together to further improve the catalyst's water resistance and hydrogenation performance, making it suitable for application in coal tar hydrogenation processes.

[0048] 3. In the gallium-modified aluminum-silicon carrier preparation method provided by this invention, the addition of organic acid increases the absolute value of the Zeta potential of the system and strengthens the electrostatic repulsion between particles, which is beneficial to the dispersion and flowability of the slurry. Simultaneously, the acidified silica flocs adsorb onto the aluminum hydroxide colloid, providing nuclei for subsequent reactions and promoting the increase in the size of the prepared carrier precursor grains. This facilitates the formation of a carrier precursor with large pore volume and large pore size coated with organic chains. The formation of hydrogen bonds between the nonionic surfactant and the hydroxyl groups of the aluminum hydroxide hydrosol prevents the particles from adhering and agglomerating, allowing the gel particles to be oriented into ordered crystal precipitates or colloidal particles with crystalline structures. Furthermore, the free silicon species can undergo ion exchange with the nonionic surfactant to form a complex, ultimately forming a mesoporous material with a stable structure. By replacing part of the framework Al with Ga, since Ga can enter the Si-O-Al framework structure like Al, the reduction of framework Al can be avoided from adversely affecting crystallinity while adjusting the acidity. This results in a silicon-aluminum material with controllable acidity. At the same time, the weak acid sites formed by framework Ga and the gallium present outside the framework can work synergistically with the strong Brønsted acid sites formed by Si-O-Al. This material is suitable for application in coal tar hydrogenation, especially in fluidized bed coal tar hydrogenation processes.

[0049] 4. The catalyst of the present invention, when applied to the coal tar hydrotreating process, exhibits high hydrogenation activity, suitable cracking activity, and good stability, effectively improving the quality and yield of the coal tar hydrotreating product oil. Detailed Implementation

[0050] The technical solutions and effects of the present invention will be further illustrated by the following embodiments, but the following embodiments do not constitute a limitation on the method of the present invention.

[0051] In this invention, unless otherwise specified, % refers to mass fraction.

[0052] In this invention, the specific surface area, pore volume, and pore distribution are measured using an ASAP2420 fully automated physical adsorption instrument from Micron Instruments, Inc.

[0053] In this invention, the XPS operating conditions are as follows: light source: MgK Alpha, energy step: 0.05 eV, scan range: 220–240 eV (molybdenum), 850–880 eV (nickel), 280–300 eV (carbon). When analyzing the valence state of molybdenum, the binding energy is determined as follows: +6 valence molybdenum species at 232–233 eV, +5 valence molybdenum species at 230–232 eV, and +4 valence molybdenum species at 228–230 eV. The proportions of +6, +5, and +4 valence molybdenum in the total Mo can be calculated using the peak areas of these three peaks.

[0054] In this invention, the catalyst composition was determined using spectrophotometry. The testing instrument was a Lambda 365 UV spectrophotometer.

[0055] In this invention, the total amount of infrared acid, the amount of L acid, and the amount of B acid are determined by infrared spectroscopy, and the instrument is a Nicot Fourier transform infrared spectrometer-6700 from the United States.

[0056] In this invention, HDS stands for hydrodesulfurization, HDO stands for hydrodeoxygenation, HDCCR stands for hydrodecarbonization, and HDM stands for hydrodemetallization.

[0057] Example 1

[0058] (1) Preparation of the carrier:

[0059] (11) Prepare an aluminum sulfate solution with a concentration of 50 g / 100 mL (based on Al2O3) and a silica sol solution with a concentration of 60 g / 100 mL (based on SiO2). The weight ratio of the silicon source (based on SiO2) to the acidic aluminum source (based on Al2O3) is 2.4:1. Add 8% citric acid to adjust the pH of the solution to 3 to obtain material AI.

[0060] (12) Add 2.0L of clean water to the reactor and heat it to 60℃. Stir at 200rad / min. Control the flow rates of material AI, 60g / 100mL sodium aluminate solution and 2mol / L gallium nitrate solution to 50mL / min, 20mL / min and 10mL / min respectively. Continuously add them to the reactor. During the reaction, control the reaction pH to 8, the reaction time to 180min and the reaction temperature to 60℃.

[0061] (13) After the precipitation reaction was complete, the temperature was raised to 95°C and the stirring rate was adjusted to 300 rad / min. A 55 g / 100 mL polyethylene glycol (molecular weight 600) solution was introduced into the reactor for hydrothermal treatment, with the nonionic surfactant added at 2.4 wt% of the alumina content of material AII. After sealing, the temperature was raised to 100°C at a rate of 15°C / min and held for 3 hours, then raised to 120°C at a rate of 10°C / min and held for 6 hours. The resulting slurry was washed with 90°C hot water until neutral, and dried at 120°C for 3 hours to obtain gallium-modified aluminum-silicon material.

[0062] (14) Weigh 448g of gallium-modified silicon-aluminum material, add 12g of guar gum powder, 9g of nitric acid and 378g of water, mix and knead into shape, dry at 140℃ for 3 hours, and calcine at 650℃ for 4 hours to obtain catalyst support A-1.

[0063] Catalyst preparation:

[0064] A first impregnation solution was prepared by mixing 58.3 g of ammonium heptamolybdate tetrahydrate, 44.9 g of ammonium sulfide, and water. The molybdenum source in the first impregnation solution contained 29 wt%. The first impregnation solution was then applied to support A-1. The impregnation was saturated. After drying at 100°C for 6 hours in air, catalyst intermediate I was obtained.

[0065] (2) Catalyst intermediate I was reacted with chlorine gas to obtain catalyst intermediate II. The purity of the chlorine gas was 98 v%. The flow rate of the chlorine gas was 3.4 mL / (min·g catalyst intermediate I). The reaction conditions were as follows: reaction temperature was 400℃, and reaction time was 90 min.

[0066] (3) The catalyst intermediate II described in step (2) is impregnated with a second impregnation solution containing nickel and phosphorus sources (37.5 g of nickel nitrate hexahydrate and 8.5 g of diammonium hydrogen phosphate dissolved in water, wherein the nickel source content in the second impregnation solution is 54 wt%). The impregnation is a saturated impregnation. After being cured at 25°C for 10 h, dried at 110°C in air for 6 h, and calcined at 510°C in nitrogen for 6 h, the catalyst C1 is obtained.

[0067] The catalyst composition, properties, and pore distribution are shown in Table 1. Group VIII metals exist in the catalyst as metal phosphides. The Mo includes +5, +6, and +4 valence Mo, i.e., Mo exists as molybdenum pentachloride, molybdenum disulfide, and molybdenum oxide. +5 valence Mo accounts for 79.0% of the total Mo atoms, +4 valence Mo accounts for 12.1%, and +6 valence Mo accounts for 8.9%.

[0068] Example 2

[0069] (1) Preparation of the carrier:

[0070] (11) Prepare an aluminum sulfate solution with a concentration of 30 g / 100 mL (based on Al2O3) and a silica sol solution with a concentration of 60 g / 100 mL (based on SiO2). The weight ratio of the silicon source (based on SiO2) to the acidic aluminum source (based on Al2O3) is 4:1. Add 10% citric acid to adjust the pH of the solution to 4 to obtain material AI.

[0071] (12) Add 2.0L of clean water to the reactor and heat it to 80℃. Stir at 250rad / min. Control the flow rates of material AI, 80g / 100mL sodium aluminate solution and 2.5mol / L gallium nitrate solution to 60mL / min, 11mL / min and 10mL / min respectively. Continuously add them to the reactor. During the reaction, control the reaction pH to 8.5, the reaction time to 90min and the reaction temperature to 80℃.

[0072] (13) After the precipitation reaction was complete, the temperature was raised to 85°C and the stirring rate was adjusted to 350 rad / min. A 60 g / 100 mL lauroyl diethanolamine solution was introduced into the reactor for hydrothermal treatment, with the nonionic surfactant added at 2.4 wt% of the alumina content of material AII. After sealing, the temperature was raised to 90°C at a rate of 10°C / min and held for 4 hours. Then, the temperature was raised to 130°C at a rate of 15°C / min and held for 4 hours. The slurry after the reaction was washed with hot water at 90°C until neutral, and dried at 130°C for 4 hours to obtain gallium-modified aluminum-silicon material.

[0073] (14) Weigh 435g of gallium-modified silicon-aluminum material, add 12g of guar gum powder, 11.2g of nitric acid and 375g of water, mix and knead into shape, dry at 120℃ for 4 hours, and calcine at 620℃ for 6 hours to obtain catalyst support B-1.

[0074] Catalyst preparation:

[0075] A first impregnation solution was prepared by mixing 54.8 g of ammonium heptamolybdate tetrahydrate, 34.3 g of thiourea, and water. The molybdenum source in the first impregnation solution contained 36 wt%. The first impregnation solution was then applied to support B-1. The impregnation was saturated. After drying at 120°C for 4 hours in air, catalyst intermediate I was obtained.

[0076] (2) Catalyst intermediate I was reacted with chlorine gas to obtain catalyst intermediate II. The purity of the chlorine gas was 97 v%. The flow rate of the chlorine gas was 4.8 mL / (min·g catalyst intermediate I). The reaction conditions were as follows: reaction temperature was 400℃, and reaction time was 65 min.

[0077] (3) The catalyst intermediate II described in step (2) was impregnated with a second impregnation solution containing nickel and phosphorus sources (34.6 g of nickel nitrate hexahydrate and 9.5 g of disodium hydrogen phosphate dissolved in water, wherein the mass content of nickel source in the second impregnation solution was 49 wt%). The impregnation was saturated impregnation. After being cured at 23°C for 12 h, dried at 120°C in air for 5 h, and calcined at 495°C in nitrogen for 6 h, the catalyst C2 was obtained.

[0078] The catalyst composition, properties, and pore distribution are shown in Table 1. Group VIII metals exist in the catalyst as metal phosphides. The Mo includes +5, +6, and +4 valence Mo, i.e., Mo exists as molybdenum pentachloride, molybdenum disulfide, and molybdenum oxide. +5 valence Mo accounts for 77.3% of the total Mo atoms, +4 valence Mo accounts for 16.5%, and +6 valence Mo accounts for 6.2%.

[0079] Example 3

[0080] (1) Preparation of the carrier:

[0081] (11) Prepare an aluminum sulfate solution with a concentration of 80 g / 100 mL (based on Al2O3) and a silica sol solution with a concentration of 40 g / 100 mL (based on SiO2). The weight ratio of the silicon source (based on SiO2) to the acidic aluminum source (based on Al2O3) is 1:1. Add 15% citric acid to adjust the pH of the solution to 3 to obtain material AI.

[0082] (12) Add 2.0L of clean water to the reactor and heat it to 80℃. Stir at 200rad / min. Control the flow rates of material AI, 75g / 100mL sodium aluminate solution and 2mol / L gallium nitrate solution to 30mL / min, 15mL / min and 10mL / min respectively. Continuously add them to the reactor. During the reaction, control the reaction pH to 9, the reaction time to 120min and the reaction temperature to 80℃.

[0083] (13) After the precipitation reaction was complete, the temperature was raised to 95°C and the stirring rate was adjusted to 400 rad / min. A 45 g / 100 mL ALEO-9 solution was introduced into the reactor for hydrothermal treatment, with the nonionic surfactant added at 2.6 wt% of the alumina content of material AII. After sealing, the temperature was raised to 100°C at a rate of 15°C / min and held for 8 hours. Then, the temperature was raised to 130°C at a rate of 10°C / min and held for 8 hours. The slurry after the reaction was washed with hot water at 90°C until neutral, and dried at 120°C for 4 hours to obtain gallium-modified aluminum silicon material.

[0084] (14) Weigh 446g of gallium-modified silicon-aluminum material, add 15g of guar gum powder, 9g of nitric acid and 363g of water, mix and knead into shape, dry at 120℃ for 5 hours, and calcine at 750℃ for 5 hours to obtain catalyst support C-1.

[0085] Catalyst preparation:

[0086] A first impregnation solution was prepared by mixing 56.9 g of ammonium heptamolybdate tetrahydrate, 48.8 g of sodium thiosulfate, and water. The molybdenum source in the first impregnation solution contained 41 wt%. The first impregnation solution was then applied to support C-1. The impregnation was saturated. After drying at 130°C for 5 hours in air, catalyst intermediate I was obtained.

[0087] (2) Catalyst intermediate I was reacted with chlorine gas to obtain catalyst intermediate II. The purity of the chlorine gas was 98 v%. The flow rate of the chlorine gas was 5.3 mL / (min·g catalyst intermediate I). The reaction conditions were as follows: reaction temperature was 350℃, and reaction time was 60 min.

[0088] (3) The catalyst intermediate II described in step (2) was impregnated with a second impregnation solution containing nickel and phosphorus sources (43.8 g of nickel nitrate hexahydrate and 7.9 g of diammonium hydrogen phosphate dissolved in water, wherein the nickel source content in the second impregnation solution was 63 wt%). The impregnation was saturated. After being cured at 23°C for 12 h, dried at 120°C in air for 6 h, and calcined at 500°C in nitrogen for 7 h, the catalyst C3 was obtained.

[0089] The catalyst composition, properties, and pore distribution are shown in Table 1. Group VIII metals exist in the catalyst as metal phosphides. The Mo includes +5, +6, and +4 valence Mo, i.e., Mo exists as molybdenum pentachloride, molybdenum disulfide, and molybdenum oxide. +5 valence Mo accounts for 77.8% of the total Mo atoms, +4 valence Mo accounts for 16.1%, and +6 valence Mo accounts for 6.1%.

[0090] Example 4

[0091] (1) Preparation of the carrier:

[0092] (11) Prepare an aluminum sulfate solution with a concentration of 65 g / 100 mL (based on Al2O3) and a silica sol solution with a concentration of 70 g / 100 mL (based on SiO2). The weight ratio of the silicon source (based on SiO2) to the acidic aluminum source (based on Al2O3) is 2:1. Add 15% citric acid to adjust the pH of the solution to 3 to obtain material AI.

[0093] (12) Add 2.0L of clean water to the reactor and heat it to 70℃. Stir at 300rad / min. Control the flow rates of material AI, 90g / 100mL sodium aluminate solution and 1.0mol / L gallium nitrate solution to 60mL / min, 25mL / min and 10mL / min respectively. Continuously add them to the reactor. During the reaction, control the reaction pH to 9, the reaction time to 150min and the reaction temperature to 70℃.

[0094] (13) After the precipitation reaction was complete, the temperature was raised to 95°C and the stirring rate was adjusted to 350 rad / min. A 60 g / 100 mL polyethylene glycol (molecular weight 400) solution was introduced into the reactor for hydrothermal treatment, with the nonionic surfactant added at 2.5 wt% of the alumina content of material AII. After sealing, the temperature was raised to 100°C at a rate of 12°C / min and held for 4 hours, then raised to 130°C at a rate of 15°C / min and held for 8 hours. The resulting slurry was washed with 90°C hot water until neutral, and dried at 140°C for 5 hours to obtain gallium-modified aluminum-silicon material.

[0095] (14) Weigh 435g of gallium-modified silicon-aluminum material, add 12g of guar gum powder, 11g of nitric acid and 375g of water, mix and knead into shape, dry at 130℃ for 5 hours, and calcine at 750℃ for 8 hours to obtain catalyst support D-1.

[0096] Catalyst preparation:

[0097] A first impregnation solution was prepared by mixing 60.5 g of ammonium heptamolybdate tetrahydrate, 45.4 g of thiourea, and water. The molybdenum source in the first impregnation solution contained 40 wt%. The first impregnation solution was then applied to support D-1. The impregnation was saturated. After drying at 130°C for 5 hours in air, catalyst intermediate I was obtained.

[0098] (2) Catalyst intermediate I was reacted with chlorine gas to obtain catalyst intermediate II. The purity of the chlorine gas was 99 v% by volume. The flow rate of the chlorine gas was 3.9 mL / (min·g catalyst intermediate I). The reaction conditions were as follows: reaction temperature was 300℃, and reaction time was 80 min.

[0099] (3) The catalyst intermediate II described in step (2) was impregnated with a second impregnation solution containing nickel and phosphorus sources (47.2 g of nickel nitrate hexahydrate and 14.3 g of diammonium hydrogen phosphate dissolved in water, wherein the nickel source content in the second impregnation solution was 67 wt%). The impregnation was saturated. After being cured at 23°C for 12 h, dried at 120°C in air for 6 h, and calcined at 500°C in nitrogen for 7 h, the catalyst C4 was obtained.

[0100] The catalyst composition, properties, and pore distribution are shown in Table 1. Group VIII metals exist in the catalyst as metal phosphides. The Mo includes +5, +6, and +4 valence Mo, i.e., Mo exists as molybdenum pentachloride, molybdenum disulfide, and molybdenum oxide. +5 valence Mo accounts for 79.0% of the total Mo atoms, +4 valence Mo accounts for 15.3%, and +6 valence Mo accounts for 5.7%.

[0101] Comparative Example 1

[0102] Compared with Example 1, the difference is that in step (11) of the carrier preparation method, no organic acid is added to adjust the pH value; the other steps are the same as in Example 1.

[0103] A comparative hydrogenation catalyst, DCA-1, was prepared. The composition, properties, and pore distribution of the catalyst are shown in Table 1.

[0104] Comparative Example 2

[0105] Compared with Example 1, the difference is that in step (13), no nonionic surfactant is added, and material AII is subjected to hydrothermal treatment alone; the other steps are the same as in Example 1.

[0106] A comparative hydrogenation catalyst, DCA-2, was prepared. The composition, properties, and pore distribution of the catalyst are shown in Table 1.

[0107] Comparative Example 3

[0108] Compared with Example 1, the difference is that gallium nitrate solution is not added in step (12) of the carrier preparation method. The other steps are the same as in Example 1.

[0109] A comparative hydrogenation catalyst, DCA-3, was prepared. The composition, properties, and pore distribution of the catalyst are shown in Table 1.

[0110] Comparative Example 4

[0111] The active metals in this catalyst include molybdenum oxide and nickel phosphide.

[0112] Compared with Example 1, in the catalyst preparation method, air is used to replace chlorine in step (2) of Example 1, that is, catalyst intermediate I reacts with air. Other steps are the same as in Example 1.

[0113] A comparative hydrogenation catalyst, DCA-4, was prepared. The catalyst composition, properties, and pore distribution are shown in Table 1. The Mo present was in the forms of +6 and +4 valence, but not +5 valence. That is, Mo existed as molybdenum disulfide and molybdenum oxide. +4 valence Mo accounted for 14.4% of the total Mo atoms, and +6 valence Mo accounted for 85.6% of the total Mo atoms.

[0114] Comparative Example 5

[0115] The active metals of the catalyst in this example include molybdenum oxide and nickel oxide. Compared with Example 1, in step (2), air is used instead of chlorine gas in Example 1, that is, catalyst intermediate I reacts with air. In step (3), no phosphorus source is added to the second impregnation solution. Other steps are the same as in Example 1.

[0116] A comparative hydrogenation catalyst, DCA-5, was prepared. The catalyst composition, properties, and pore distribution are shown in Table 2. The Mo present is in the +6 and +4 valence states, and does not contain +5 valence Mo. That is, Mo exists in the form of molybdenum disulfide and molybdenum oxide. +4 valence Mo accounts for 14.2% of the total Mo atoms, and +6 valence Mo accounts for 85.8% of the total Mo atoms.

[0117] Application examples

[0118] The catalysts obtained in the examples and comparative examples were evaluated using the feedstock oils listed in Table 2. The properties of the feedstock oils and reaction conditions are shown in Table 2. Oil samples were taken and analyzed after 1000 hours of operation, and the evaluation results are shown in Table 3. The sulfidation conditions were as follows: the sulfidation liquid was hydrotreated diesel containing 10.0% DMDS by mass; the flow rate of the sulfidation liquid was 25.0 mL / (h·g catalyst); the hydrogen pressure was 14.0 MPa; the hydrogen flow rate was 120.0 mL / (min·g catalyst); the low-temperature sulfidation stage started at 25°C with a heating rate of 9.0°C / h, and was held at 230°C for 8.0 h; the high-temperature sulfidation stage started at 230°C with a heating rate of 10.0°C / h, and was held at 380°C for 6.0 h, after which sulfidation was completed.

[0119] Table 1. Composition and properties of catalysts in the examples and comparative examples.

[0120]

[0121]

[0122] Table 2. Properties of feedstock oil and reaction conditions

[0123] properties of crude oil <![CDATA[Density (20°C) / kg·m -3 > 1104.5 S / wt% 0.23 <![CDATA[Fe+Ca / μg·g -1 ]]> 258.4 CCR / wt% 15.2 O / wt% 7.6 Reaction conditions Reaction temperature / ℃ 368 Reaction pressure / MPa 14.5 <![CDATA[Liquid hourly space velocity / h -1 > 0.46 Hydrogen-to-oil volume ratio 650

[0124] Table 3. Activity evaluation results of each catalyst example.

[0125]

[0126] The specific embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A coal tar hydrogenation catalyst, comprising a support and an active metal component; wherein the support is a gallium-modified silica-alumina support; wherein, based on the mass of the gallium-modified silica-alumina support, the mass content of gallium oxide is 2.0%~5.0%, the mass content of silicon dioxide is 20.0%~60.0%, and the mass content of alumina is 35.0%~78.0%; The active metal component includes Mo and Group VIII metal elements; the Mo includes +5 valence Mo; the Group VIII metal elements exist in the catalyst in the form of metal phosphides; The catalyst has the following properties: specific surface area of ​​150~200 m². 2 / g, pore volume is 0.5~0.8mL / g, total acid content is 0.2~0.5mmol / g, and the ratio of B acid content to L acid content is 0.35~0.65; The catalyst has the following pore size distribution: pores with a diameter <10 nm account for 5%~10% of the total pore volume, pores with a diameter of 10~50 nm account for 65%~80% of the total pore volume, and pores with a diameter >50 nm account for 10%~30% of the total pore volume. Mo also includes +4 valence M and +6 valence Mo; +5 valence Mo accounts for more than 50% of total Mo by atomic count; +5 valence Mo is molybdenum pentachloride; +4 valence Mo is molybdenum disulfide; +6 valence Mo is molybdenum oxide.

2. The catalyst according to claim 1, characterized in that, +5 valence Mo accounts for 55% to 80% of total Mo atoms.

3. The catalyst according to claim 2, characterized in that, The group VIII metal element is selected from one or more of Fe, Co, and Ni.

4. The catalyst according to claim 3, characterized in that, The group VIII metal element is selected from at least one of Co and Ni.

5. The catalyst according to claim 3, characterized in that, The group VIII metal element is selected from Ni.

6. A method for preparing the catalyst according to any one of claims 1 to 5, comprising: (1) A first impregnation solution is obtained by mixing molybdenum source, sulfur source and water, and then impregnated on a support. After drying, catalyst intermediate I is obtained. (2) React the catalyst intermediate I described in step (1) with chlorine gas to obtain catalyst intermediate II; (3) The group VIII metal element is selected from nickel. The catalyst intermediate II described in step (2) is impregnated with a second impregnation solution containing nickel source and phosphorus source, and then cured, dried and calcined to obtain the catalyst.

7. The method according to claim 6, characterized in that, The method for preparing the carrier includes: (11) Mix and stir the acidic aluminum salt aqueous solution, silicon source, and organic acid to obtain material AI; (12) Material AI is subjected to a precipitation reaction with gallium-containing solution and alkaline aluminum salt aqueous solution in parallel flow to obtain material AII; (13) The material AII was subjected to hydrothermal treatment with a nonionic surfactant to obtain gallium-modified aluminum silicon material; (14) The gallium-modified silicon-aluminum material, adhesive, extrusion aid and water obtained in step (13) are mixed and kneaded, dried and calcined to obtain the catalyst support.

8. The method according to claim 7, characterized in that, In step (11), the organic acid is one or more of maleic acid, fumaric acid, adipic acid, tartaric acid, citric acid, oxalic acid, acetic acid, salicylic acid, and malic acid. And / or, the mass concentration of the organic acid is 7% to 16%; And / or, the amount of organic acid added makes the pH value of the material AI 2 to 4.

9. The method according to claim 8, characterized in that, The amount of organic acid added makes the pH value of the material AI 3~4.

10. The method according to claim 7, characterized in that, In step (12), the gallium-containing solution is a gallium nitrate solution with a concentration of 0.5~2.5 mol / L; And / or, the alkaline aluminum salt is at least one of sodium aluminate or potassium aluminate; And / or, the concentration of the alkaline aluminum salt aqueous solution, calculated as Al2O3, is 20~100g / 100mL; And / or, the ratio of the co-flow rates of the gallium-containing solution, the material AI, and the alkaline aluminum salt aqueous solution is 1:3~7:1~3; And / or, the reaction temperature is 60~90℃, the reaction time is 60~180 minutes, and the pH value is 8.0~9.

7.

11. The method according to claim 10, characterized in that, In step (12), the reaction is carried out under stirring conditions, and the stirring rate is 100 to 500 rad / min.

12. The method according to claim 11, characterized in that, In step (12), the stirring rate is 150 to 450 rad / min.

13. The method according to claim 7, characterized in that, In step (13), the nonionic surfactant is selected from one or more of polyethylene glycol, alkylolamide, and polyether; And / or, the alkylolamide is one or more of lauroyl diethanolamine and coconut oil fatty acid diethanolamide; And / or, the polyether is one or more of AEO-6 and AEO-9; the polyethylene glycol has a molecular weight of 200 to 1000; And / or, the amount of the nonionic surfactant added is 0.1% to 5% of the mass of material AII obtained in step (12) based on alumina; And / or, the concentration of the nonionic surfactant is 30~70g / 100mL.

14. The method according to claim 13, characterized in that, In step (13), the molecular weight of the polyethylene glycol is 200-700; And / or, the amount of the nonionic surfactant added is 0.5% to 3% of the mass of the material AII obtained in step (12) based on alumina.

15. The method according to claim 7, characterized in that, In step (13), the conditions for hydrothermal treatment are as follows: the hydrothermal treatment temperature is 80~130℃, the time is 3~18 hours, and the heating rate is 8~15℃ / min.

16. The method according to claim 15, characterized in that, In step (13), the hydrothermal treatment adopts two stages of hydrothermal treatment. The temperature of the first stage of hydrothermal treatment is 80~110℃ and the time of the first stage of hydrothermal treatment is 1~9 hours. The temperature of the second stage of hydrothermal treatment is 100~130℃ and the time of the second stage of hydrothermal treatment is 1~9 hours. The temperature of the second stage of hydrothermal treatment is at least 15℃ higher than that of the first stage of hydrothermal treatment.

17. The method according to claim 15, characterized in that, In step (13), the temperature of the second stage of hydrothermal treatment is at least 20°C higher than that of the first stage of hydrothermal treatment.

18. The method according to claim 6, characterized in that, In step (1), the molybdenum source is selected from at least one of ammonium dimolybdate, ammonium tetramolybdate dihydrate, and ammonium heptamolybdate tetrahydrate; And / or, the sulfur source is selected from at least one of thiourea, ammonium sulfide, thioacetamide and sodium thiosulfate; And / or, the mass ratio of the molybdenum source to the sulfur source is 3~5:2~4; And / or, the molybdenum source in the first impregnation solution has a mass content of 25wt% to 45wt%.

19. The method according to claim 6, characterized in that, In step (2), the purity of the chlorine gas is 96% or higher by volume fraction; the flow rate of the chlorine gas is 2.7~6.8 mL / (min·g catalyst intermediate I). And / or, the reaction conditions are as follows: reaction temperature is 300~400℃, and reaction time is 40~90min.

20. The method according to claim 6, characterized in that, In step (3), the nickel source is a soluble nickel salt; And / or, the phosphorus source is selected from at least one of ammonium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, and phytic acid; And / or, in the second impregnation solution, the molar ratio of nickel source (calculated as metal element) to phosphorus source (calculated as phosphorus element) is 0.3~3:1; And / or, in the second impregnation solution, the mass content of the nickel source is 40wt%~68wt%.

21. The method according to claim 6, characterized in that, In step (3), the nickel source is at least one of nickel nitrate, monohydrogen phosphate, and dihydrogen phosphate.

22. The use of the catalyst according to any one of claims 1 to 5 or the catalyst prepared by any one of claims 6 to 21 in the hydrotreating of coal tar.

Citation Information

Patent Citations

  • Combined technology for producing clean fuel oil by hydrogenation of coal tar and catalyst thereof

    CN101885984A

  • Boiling bed coal tar hydrotreating-hydrocracking composite catalyst and preparation method thereof

    CN108686702A

  • Residual oil hydrotreating method

    CN114644937A

  • Coal tar hydrogenation catalyst and preparation method thereof

    CN114749194A